Environmental threats and conservation implications for Atlantic salmon and brown trout during their critical freshwater phases of spawning, egg development and juvenile emergence - Smialek, Nicole; Pander, Joachim; Geist, Juergen (Fisheries management and ecology, 2021)
Atlantic salmon Salmo salar L. and brown trout Salmo trutta fario L. are species of high socio‐economic and ecological value. Declining populations make them target species of fisheries management. This paper reviews the direct effects of deficient longitudinal connectivity, changes in discharge, high water temperatures, oxygen depletion, changes in water chemistry and increasing loads of fine sediment on the critical life stages of spawning, egg incubation and emergence. It further provides an overview about the basic autecological requirements of Atlantic salmon and brown trout and summarises important thresholds of physico‐chemical tolerances. This collection of information provides important baselines for assessing historical, ongoing and new threats relevant for the management of both species in fresh waters. Critical early‐life stages of both species are almost identical, creating synergies in conservation and restoration. Seaward‐migrating forms are exposed to further stressors, but improving starting conditions can also greatly improve their resilience.